PENGARUH FASILITAS BELAJAR TERHADAP HASIL BELAJAR SISWA DI SMAN 1 TELUK KUANTAN KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Santika, Fiska; Johan, Rina Selva; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack : The objectives of this research were to know the effect of learning facilities that used by student of class X, dan XI IPS in SMAN 1 Teluk Kuantan Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi. The population of this research was the class X dan XI IPS SMAN 1 Teluk Kuantan amount 209 people and the sample amount 137 people. The collected data used questionnaire and documentation. Data analysis of this research used simle linier regression. Research result based on simple linier regression showed that the using of learning facilities influence on student learning outcomes of class X dan XI IPS in SMAN 1 Teluk Kuantan this can be seen from a constant value (a) of 46,000 and the value coefisien regression (b) of 0,351 with a regresiion equation 46,000 + 0,351. According the calculation of R (R squer change) obtained a value of 0,392. It means that the contribution of the influence of the use learning facilities on learning outcomes by 39,2%.Key word : Learning facilities, learning outcomes